2000
DOI: 10.1212/wnl.54.12.2205
|View full text |Cite
|
Sign up to set email alerts
|

Practice parameter: Risk of driving and Alzheimer’s disease (an evidence-based review) [RETIRED]

Abstract: Article abstract-Studies of automobile accident frequency among drivers with AD have yielded conflicting results about the risk of accidents. To develop a practice parameter regarding driving and AD the authors performed a systematic review of the literature. The authors identified well-designed, controlled studies of driving and AD using the National Library of Medicine's MEDLINE database. The authors also compared the relative rates of crashes and other performance measurements of driving ability in the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
1
4

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 286 publications
(103 citation statements)
references
References 23 publications
4
94
1
4
Order By: Relevance
“…41,47 The CDR is scored from 0 to 2. Higher scores reflect a greater impairment in cognitive functional abilities of daily living.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…41,47 The CDR is scored from 0 to 2. Higher scores reflect a greater impairment in cognitive functional abilities of daily living.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…Higher scores reflect a greater impairment in cognitive functional abilities of daily living. 47 Alzheimer's patients with a CDR score of >1.0 have been shown to have a higher risk of collisions and should be advised not to drive. Patients with a score of 0.5 should be evaluated every 6 months and undergo a formal driving examination.…”
Section: Methods Of Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we addressed this question for drivers with dementia, through a systematic literature review. 1 This evidence-based medicine practice parameter reported that there was an increased risk of collisions for drivers with a clinical dementia rating scale score of 0.5 (possible Alzheimer's disease) and 1 (probable Alzheimer's disease) compared to nondemented drivers. The clinical dementia rating is a complex rating scale, based on a structured interview, encompassing many domains, and not easily adaptable to a brief clinical encounter.…”
mentioning
confidence: 99%